The Challenge of Good and Correct Indonesian Language in Higher Education - Barirohmah Barirohmah; Nurmahmi Nurmahmi; Sedya Santosa (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Higher education is the center of civilization in modern society. Universities become centers for the development of science and technology. Higher education is a place to shape the character, personality, independence, and skills of human resources in Indonesia. It is the community in the university environment that will lead the direction of national development in the future. Indonesia, which consists of islands, requires a unifying language to communicate in all corners of the country. Indonesian as the national language, which was confirmed at the 1928 Youth Pledge, was able to become a unifying language for the nation. The era of globalization has an influence on the use of Indonesian in communication. The existence of globalization of course has an impact on world communication which requires an international language to exchange scientific information. This is a challenge for the Indonesian language to remain the identity of the Indonesian nation. Pride in using foreign languages ​​in communication and lack of pride in their own language will trigger the erosion of national identity. Character education that has the personality of the Indonesian nation must be instilled in the younger generation so that national identity is maintained.